Evaluation of Biomarkers of Bone Metabolism on Salivary Matrix in the Remodeling of Periodontal Tissue during Orthodontic Treatment - Angela Pia Cazzolla; Vincenzo Brescia; Roberto Lovero; Antonietta Fontana; Arcangela Giustino; Mario Dioguardi; Maria Severa Di Comite; Francesca Di Serio; Domenico Ciavarella; Vito Crincoli (MDPI AG, 2024)
The aim of this study was to evaluate changes in the concentration of N-terminal type I collagen extension pro-peptide (PINP), tartrate-resistant acid phosphatase (TRAcP), and parathyroid hormone-related protein (PTHrP) in saliva during orthodontic treatment in order to evaluate whether changes in bone turnover marker (BTM) concentration can help highlight the effects of orthodontic mechanical loading in the absence of clinical evidence of tooth movement in terms of tooth movement. Saliva samples from 25 apparently healthy young subjects (10 females and 15 males) were collected using Salivette® (Sarstedt) with cotton swabs and the concentrations of PTHrP, TRAcP 5b, and PINP were analyzed at time 0 (T1), 25 days (T2), and at 45 days (T3). Differences in the median value of biomarker levels between baseline T1 and follow-up of the different groups (T2 and T3) were assessed using the non-parametric Mann-Whitney U test. Trough concentrations of P1NP, PTHrP, and TRAcP were 0.80 µg/L, 0.21 ng/mL, and 0.90 U/L above the method LOD. The non-parametric Mann-Whitney U test confirmed a statistically significant difference in T1 versus concentrations of T2 and T3. All subjects evaluated had a statistically significant difference between T1 vs. T3. when compared with the specific critical difference (RCV) for the analyte The results obtained demonstrate that the evaluation of BTM changes in saliva can help the evaluation of orthodontic procedures and the monitoring of biomechanical therapy.